Listening to the Enemy: Challenging The National Narrative of World War II in Contemporary Norwegian Fiction - Torjusen, Henrik (Scandinavistica Vilnensis, 2023)
This article analyses five Norwegian novels that all incorporate German soldiers’ experiences as an important part of the Norwegian story of World War II. Abandoning the strong focus on antagonistic relationships of previous narratives, the five novels analysed in this article represent a new approach to the history of the war that aims to view the enemy through what Bull and Hansen (2016) have called agonistic memory, which includes the perspective of the perpetrator to understand conflicts. Previously, when Norwegian authors included German soldiers in narratives about World War II, it was part of a general portrait of the enemy. The individual soldier has few distinct features and no independent identity. These portraits followed the hegemonic Norwegian narrative of the occupation: The good Norwegians, who were part of the home front, versus the Germans and the morally inferior Norwegians who supported them. However, in the last ten years, several novels have revisited the war narrative through representations of previously neglected groups, one of which is the German soldier. The five novels have quite different approaches, but they all question the traditional Norwegian war narrative through complex representations of the enemy. My analysis of the five texts will identify how the texts challenge the conventional history of the occupation through an agonistic perspective that aims to revisit how the war is remembered. These representations of the German soldiers are a central part of the new examination of the long shadows cast by the memories of war in Norway.